Celiac disease in paediatric patients in the United Arab Emirates: a single-center descriptive study - AlNababteh, Asma H.; Tzivinikos, Christos; Al-Shamsi, Saif; Govender, Romona Devi; Al-Rifai, Rami H. (Frontiers in Pediatrics, 2023)
Introduction: Celiac disease (CD) is an autoimmune disorder that is provoked by the consumption of gluten in genetically vulnerable individuals. CD affects individuals worldwide with an estimated prevalence of 1% and can manifest at any age. Growth retardation and anemia are common presentations in children with CD. The objective of this study is to estimate the prevalence of CD in multiple “at risk groups” and to characterize children with CD, presented to a tertiary hospital in Dubai, United Arab Emirates (UAE). Methods: The study reviewed medical charts of all patients <18 years who had received serologic testing for CD. The study was conducted at Al Jalila Children’s Specialty Hospital in Dubai, UAE, from January 2018 to July 2021. Extracted information from medical records included sociodemographics, laboratory findings, clinical presentation, and any associated co-morbidities. The European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) criteria were used to identify patients with CD. Results: During the study period, 851 paediatric patients underwent serological screening for CD, out of which, 23 (2.7%) were confirmed with CD. Of the 23 patients diagnosed with CD, 43.5% had no gastrointestinal symptoms. Diabetes type 1 (30.4%) followed by iron deficiency anaemia (30%) and Hashimoto thyroiditis (9%) were the most commonly associated comorbidities. The prevalence of CD among paediatric patients with autoimmune thyroiditis (12.5%) was 1.92-times higher than that among paediatric patients with diabetes type 1 (6.5%). Conclusion: The results of this study show that almost three out of every 100 paediatric patients who were screened for CD were confirmed to have the condition. These findings highlight the importance of screening children who are at risk or present symptoms suggestive of CD, to ensure early diagnosis and appropriate management.